2020 American College of Rheumatology Guideline for the Management of Gout. Issue 6 (11th May 2020) - FitzGerald, John D.; Dalbeth, Nicola; Mikuls, Ted; Brignardello‐Petersen, Romina; Guyatt, Gordon; Abeles, Aryeh M.; Gelber, Allan C.; Harrold, Leslie R.; Khanna, Dinesh; King, Charles; Levy, Gerald; Libbey, Caryn; et al.
Abstract : Objective: To provide guidance for the management of gout, including indications for and optimal use of urate‐lowering therapy (ULT), treatment of gout flares, and lifestyle and other medication recommendations. Methods: Fifty‐seven population, intervention, comparator, and outcomes questions were developed, followed by a systematic literature review, including network meta‐analyses with ratings of the available evidence according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology, and patient input. A group consensus process was used to compose the final recommendations and grade their strength as strong or conditional. Results: Forty‐two recommendations (including 16 strong recommendations) were generated. Strong recommendations included initiation of ULT for all patients with tophaceous gout, radiographic damage due to gout, or frequent gout flares; allopurinol as the preferred first‐line ULT, including for those with moderate‐to‐severe chronic kidney disease (CKD; stage > 3); using a low starting dose of allopurinol (≤100 mg/day, and lower in CKD) or febuxostat (< 40 mg/day); and a treat‐to‐target management strategy with ULT dose titration guided by serial serum urate (SU) measurements, with an SU target of <6 mg/dl. When initiating ULT, concomitant antiinflammatory prophylaxis therapy for a duration of at least 3–6 months was strongly recommended. For management of gout flares, colchicine, nonsteroidal antiinflammatory drugs, or glucocorticoids (oral, intraarticular, or intramuscular) were strongly recommended. Conclusion: Using GRADE methodology and informed by a consensus process based on evidence from the current literature and patient preferences, this guideline provides direction for clinicians and patients making decisions on the management of gout.